An Examination of Suicidal Behavior among Black College Students with Exposure to Police Violence. Issue 1 (11th November 2022) - Szlyk, Hannah; Motley, Robert; Joe, Sean; Nonas-Barnes, Lucy; Azasu, Enoch
Abstract: There is limited research about suicidal behaviors among Black emerging adults (peak age of suicide risk) who report exposure to police violence. The current study applies an integrated approach to examine individual, immediate environment, and community-based risk and protective factors of suicide among Black college students who reported previous exposure to police violence. A purposive sample of Black college students ( N = 300) was analyzed using bivariate analyses and binary logistic regression. Outcome variables investigated were lifetime suicidal ideation and suicide attempt. Twenty-eight percent of participants reported lifetime suicidal ideation and 14 percent reported lifetime attempts. Female students were significantly more likely to report lifetime suicidal ideation and recent symptoms of anxiety and to engage in emotional social support than male peers. Logistic regression results demonstrated that higher income and greater depression symptoms were associated with lower reporting of lifetime suicidal ideation. Reporting of more grit, the trait of perseverance and passion for long-term goals, was associated with a lower reporting of both lifetime suicidal ideation and suicide attempt. Findings have implications for how social workers in higher education are encouraged to address suicidal behavior among Black students, including the cultivation of grit.